Analisis Pascakolonialisme Gadis Pantai Karya Pramoedya Ananta Toer dalam Teori Homi K. Bhabha - Ummu Fatimah Ria Lestari (Balai Bahasa Sumatera Utara, 2019)
This research discusses about the identity forms of postcolonial in Gadis Pantai by Pramoedya Ananta Toer. It was analyzed by Homi K. Bhabas postcolonial theory. The goal of this research is to describe and to analyze the postcolonial identity forms in Gadis Pantai that written by Pramoedya Ananta Toer. The result of this research can support literary works, especially postcolonial study and its using in literary research. The method of this research is descriptive qualitative. It was done by some ways, it consist of to collect data, to manage data, and to analyze data. Then the data was managed and analyzed. Analyzing data used the deconstruction method. This research took some conclusions, they are 1) the postcolonial identity consists of stereotype, mimicry, hybrid, and ambivalence was found on novel, 2) the colonizer created stereotype if their colony people is just their slaves. The colony people do mimicry by to imitate about fashion, foods, and game of the colonizer. The hybrid between the colonizer and colony people was found in drinking coffee style, using shoes, culinary, and tools of eat. Ambivalence in this novel was found in character Bendoro and